Analisis Akad Peminjaman Uang Melalui Aplikasi Pinjaman Adakami dalam Perspektif Ekonomi Islam - Cantika Suhardiman Putri, Radya; Muhammad Muchlis, Madian (CV. Lafadz Jaya, 2024)
AbstractThis research examines the Islamic Economics perspective on online loans, primarily through the Adakami application. This study aims to reveal Islamic views on online loans, understand the money lending system on the Adakami application, and determine whether Adakami online loans comply with Islamic law. This examination uses a qualitative descriptive methodology. The data was from scientific articles and news about online lending law in Islam and the Adakami platform. The findings of this research reveal that Muslims are allowed to borrow online but must follow established Sharia principles. The principles that must be taken into account include that the borrower is due, the loan item is an item that can be counted, the loan item can be used per Sharia, there is a handover process (ijab-kabul), and there are no additional benefits for any party. The Adakami platform violates one of the existing Sharia laws: taking advantage of the lending party (riba) by charging interest on loans. Therefore, online borrowing using the Adakami application is not allowed in Islam.